Desulfurization Of Illinois No. 6 Coals With Sodium Hypochlorite - E. Cho (Society for Mining, Metallurgy & Exploration, 2007)
Illinois No. 6 coals of IBC 101 and IBC 112 were treated in solution with sodium hypochlorite to remove their sulfur contents, especially organic sulfur. The lab experiments were conducted in two steps of leaching at room temperature and hydrolysis at 90oC. The removal of organic sulfur from IBC 101 was by 37.8% while that from IBC 112 was only 13.7% under their respective optimum conditions. This large difference in organic sulfur removal is considered to be due to difference in concentration of surface total acid group, 3.14 vs. 0.88 mmol/g of coal.